Produção e avaliação de vídeos didáticos como ferramenta de aprendizagem ativa nas aulas de biologia - D'andréa, Rosicléa Maria Santos (2020)
Biology teaching currently faces the challenge of modernizing in a world in constant transformation, especially concerning the development and use of new educational technologies. The use of new learning methodologies in Biology classes is an active tool for student-centered learning. This work was developed at the Federal Institute of Paraíba (IFPB) and aimed to evaluate the process of producing short didactic videos by students from the Vocational Course in Mechanics at the high school level as a tool for active learning in Biology classes. The research’s approach was characterized as qualitative and quantitative, as participant in terms of procedures, as action-research in terms of objectives and as field research in terms of object. Face to face activities and virtual environments were used to guide students in the stages of video production. Students were assessed through pre-test, post-test, participation questionnaire and self-assessment forms. The developed activities improved student skills such as teamwork, interaction to solve problems, organization, cooperation, interest, and responsibility. The video production made it possible to design Cine-Bio, a didactic platform hosted at IFPB’s João Pessoa campus official video channel and made available to any interested user. As a product of this research, a methodological guide was generated to produce short videos to be used by teachers and their students. The active participation of students in the production of videos has shown that this tool is suitable for student-centered learning.